PREDICTION AS AN OUTRUNNING KIND OF COGNITION - Fotini Fedorovna Poshnagidi (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the future prediction problem in all spheres of life. The given phenomenon is profoundly and successively observed in different historic periods. The actor analysis the given problem from viewpoint of prediction signisicanc in progresses development of society emphasizes its relevance in today’s society.